Study on the Impact of Institutional Investors' Shareholding on Corporate Carbon Emissions - Chen, Xinyu; An, Zhiyu (Transactions on Economics, Business and Management Research, 2024)
As the global climate change problem is becoming more and more serious, reducing carbon emissions has become an important task for the sustainable development of enterprises. As an important participant in the capital market, the shareholding behaviour of institutional investors will have an important impact on the decision-making and behaviour of enterprises. In this paper, A-share industrial enterprises are selected as research samples from 2014 to 2022 to empirically test the impact of institutional investors' shareholding on corporate carbon emissions. It is found that institutional investor shareholding can significantly reduce corporate carbon emissions. In terms of classification, compared with sensitive institutional investors, pressure-resistant institutional investors represented by funds, social security funds, QFIIs, and enterprise annuities have a more obvious inhibiting effect on corporate carbon emissions. The study in this paper can help us to promote enterprises to pay more attention to carbon emissions from a micro perspective, improve the long-term value of enterprises, and help to achieve the dual-carbon goal in China.